Becoming-Rhythm: A Rhizomatics of the Girl. - Jones, Leisha (Deleuze Studies, 2011)
I appropriate Deleuze and Guattari's concept of the refrain for a feminist analysis of the girl because it offers more insight into the ways girls construct themselves as performative networks than the death-by-culture or at-risk model preferred by such feminists as Jean Kilbourne, Carol Gilligan, and even Susan Bordo. I proffer that it costs women everything to practise a politics of difference that is by definition reactionary, a reaction to the cultural refusal of leaky gendered bodies that must be overcome. Girl is mapped through such alternations as powerful aggregates of the tremulous, roaming emissions of monstrous particles most desired and desirous.